Metode Pembelajaran Tahfizh Alquran Di Pesantren ‘Ulumul Qur’an Mardhatillah Kota Subulussalam - Neliwati; Afda, Miranti Adelia; Helmi, Nur (Transformasi Manageria Journal of Islamic Education Management, 2024)
This study aims to find or describe the enthusiasm of students for memorizing the Koran at the 'Ulumul Qur'an Mardhatillah Subulussalam Islamic Boarding School, teachers use several methods in teaching students to memorize the Koran easily so they can increase their enthusiasm for memorizing the Koran. The methods taught by the teacher when teaching them to memorize the Koran include: reading carefully verses from the verses of the Koran that will be memorized by looking at the manuscript repeatedly, memorizing verses from verses repeatedly so that they are finally memorized, depositing or listening to memorization. that a student has just memorized to a teacher (talaqqi), repeats the memorization of the Koran bit by bit which has been deposited with the teacher (tikrar), and listens to the memorization that has been memorized to other people, either to friends or other congregations (tasmi'). Keywords : method, learning. tahfizh of the koran